Differential resilience of chickpea’s reproductive organs to cold stress across developmental stages: insights into antioxidant strategies for enhanced fertility - Padhiar, Deeksha; Kaur, Sarbjeet; Jha, Uday Chand; Prasad, P. V. Vara; Sharma, Kamal Dev; Kumar, Sanjeev; Parida, Swarup Kumar; Siddique, Kadambot H. M.; Nayyar, Harsh (Frontiers in Plant Science, 2025)
Chickpea is highly sensitive to cold stress during its reproductive stages, leading to significant reductions in potential pod formation due to decreased reproductive success. This study aimed to investigate the specific responses of anthers and ovules to cold stress, explore the role of oxidative stress and antioxidant mechanisms, and understand the relationship between oxidative stress and reproductive function to enhance our understanding of chickpea responses to cold stress. Chickpea seeds of contrasting genotypes—cold-tolerant (ICC 17258, ICC 16349) and cold-sensitive (ICC 15567, GPF 2)—were sown outdoors in early November under optimal conditions (25.5/15.4°C mean day/night temperatures). At 50 days after sowing, plants were subjected to 13/7°C cold stress (12 h light/dark in walk-in growth chambers. Cold stress significantly increased membrane damage and reduced cellular viability in anthers and ovules, particularly in cold-sensitive (CS) genotypes. Oxidative damage was more pronounced in anthers, particularly at anthesis (stage 2), as indicated by elevated malondialdehyde and hydrogen peroxide levels. Cold-tolerant (CT) genotypes exhibited increased antioxidant activity under stress, especially at pre-anthesis (stage 1), followed by declines at later stage, although responses varied by genotype. Anthers exhibited higher overall antioxidants activity than ovules, while ovules demonstrated notably high catalase activity. Among the antioxidants studied, ascorbate peroxidase and glutathione reductase were most prominent in the CT genotype, along with higher levels of ascorbate (AsA) and glutathione (GSH), highlighting the critical role of the AsA–GSH cycle in conferring cold tolerance to chickpea. Exogenous supplementation with 1 mM ascorbate (AsA) and glutathione (GSH) significantly stimulated pollen germination in cold-stressed plants under in vitro conditions, with a greater effect observed in CS genotypes. Furthermore, antioxidant activity strongly correlated with key reproductive traits such as pollen germination and ovule viability. This study revealed that the anthers and ovules exhibited distinct responses to cold stress, with significant genotypic differences across key reproductive stages. These insights provide a deeper understanding of cold tolerance mechanisms in chickpea and provide vital clues for breeding strategies to enhance resilience and reproductive success under cold stress.